Association of salivary parameters and erosive tooth wear in preschool children - Mayra Manoella PEREZ; Ana Clara Magalhães LUS; Priscila Hernandez CAMPOS; Stella Ferreira do AMARAL; Adrian LUSSI; Michele Baffi DINIZ; Renata Oliveira GUARÉ (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aims of this study were to 1) assess the association between erosive tooth wear (ETW) according to the BEWE (Basic Erosive Wear Examination) scoring system and salivary parameters and 2) compare salivary parameters according to ETW severity in the subgroup of children with ETW. This cross-sectional study included 52 preschool children aged 5 years paired by sex. A calibrated examiner assessed ETW using BEWE criteria, and stimulated saliva was collected to determine salivary flow, osmolality, pH, and buffering capacity. The children were divided into two groups: without ETW (n=26; BEWE score 0) and with ETW (n=26; BEWE scores 1 and 2). Logistic regression analysis was used to determine the magnitude of the association between ETW and salivary parameters and estimates of odds ratios (OR). In the unadjusted analysis, the ETW group was more likely to have lower salivary flow (OR = 0.079; 95%CI = 0.013-0.469; p = 0.005) and lower osmolality (OR = 0.993; 95%CI = 0.985-1.000; p = 0.049). In the adjusted analysis, salivary flow remained significantly associated with ETW (OR = 0.087; 95%CI = 0.014-0.533; p = 0.008). Lower salivary osmolality values were observed in ETW, especially in preschool children with more severe ETW (BEWE score 2). Receiver operating characteristic (ROC) determined a salivary osmolality cutoff point of < 201 for the presence of ETW. In conclusion, salivary flow rate was significantly associated with ETW prevalence. Lower values of salivary osmolality were observed in preschool children with distinct erosive lesions with significant loss of tooth structure (BEWE 2).